Treatment of advanced gastroenteropancreatic neuroendocrine neoplasia, are we on the way to personalised medicine?. Issue 9 (10th March 2021) - Rinke, Anja; Auernhammer, Christoph J; Bodei, Lisa; Kidd, Mark; Krug, Sebastian; Lawlor, Rita; Marinoni, Ilaria; Perren, Aurel; Scarpa, Aldo; Sorbye, Halfdan; Pavel, Marianne Ellen; Weber, Matthias M; et al.
Abstract : Gastroenteropancreatic neuroendocrine neoplasia (GEPNEN) comprises clinically as well as prognostically diverse tumour entities often diagnosed at late stage. Current classification provides a uniform terminology and a Ki67-based grading system, thereby facilitating management. Advances in the study of genomic and epigenetic landscapes have amplified knowledge of tumour biology and enhanced identification of prognostic and potentially predictive treatment subgroups. Translation of this genomic and mechanistic biology into advanced GEPNEN management is limited. 'Targeted' treatments such as somatostatin analogues, peptide receptor radiotherapy, tyrosine kinase inhibitors and mammalian target of rapamycin inhibitors are treatment options but predictive tools are lacking. The inability to identify clonal heterogeneity and define critical oncoregulatory pathways prior to therapy, restrict therapeutic efficacy as does the inability to monitor disease status in real time. Chemotherapy in the poor prognosis NEN G3 group, though associated with acceptable response rates, only leads to short-term tumour control and their molecular biology requires delineation to provide new and more specific treatment options. The future requires an exploration of the NEN tumour genome, its microenvironment and an identification of critical oncologic checkpoints for precise drug targeting. In the advance to personalised medical treatment of patients with GEPNEN, clinical trials need to be based on mechanistic and multidimensional characterisation of each tumour in order to identify the therapeutic agent effective for the individual tumour. This review surveys advances in NEN research and delineates the current status of translation with a view to laying the basis for a genome-based personalised medicine management of advanced GEPNEN.